Effects of age and hearing loss on the recognition of emotions in speech - Christensen, Julie A (Ear Hear, 2019)
OBJECTIVE: Emotional communication is a cornerstone of social cognition and informs human interaction. Previous studies have shown deficits in facial and vocal emotion recognition in older adults, particularly for negative emotions. However, few studies have examined combined effects of aging and hearing loss on vocal emotion recognition by adults. The objective of this study was to compare vocal emotion recognition in adults with hearing loss relative to age-matched peers with normal hearing. We hypothesized that age would play a role in emotion recognition and that listeners with hearing loss would show deficits across the age range. DESIGN: Thirty-two adults (22-74 years of age) with mild to severe, symmetrical sensorineural hearing loss, amplified with bilateral hearing aids and 30 adults (21-75 years of age) with normal hearing, participated in the study. Stimuli consisted of sentences spoken by two talkers, one male, one female, in 5 emotions (angry, happy, neutral, sad, and scared) in an adult-directed manner. The task involved a single-interval, five-alternative forced-choice paradigm, in which the participants listened to individual sentences and indicated which of the 5 emotions was targeted in each sentence. Reaction time was recorded as an indirect measure of cognitive load. RESULTS: Results showed significant effects of age. Older listeners had reduced accuracy, increased reaction times, and reduced d’ values. Normal hearing listeners showed an Age by Talker interaction where older listeners had more difficulty identifying male vocal emotion. Listeners with hearing loss showed reduced accuracy, increased reaction times, and lower d’ values compared to age-matched normal hearing listeners. Within the group with hearing loss, age and talker effects were significant, and low frequency pure tone averages showed a marginally significant effect. Contrary to other studies, once hearing thresholds were taken into account, no effects of listener sex were observed, nor were there effects of individual emotions on accuracy. However, reaction times and d’ values showed significant differences between individual emotions. CONCLUSIONS: The results of this study confirm existing findings in the literature showing that older adults show significant deficits in voice emotion recognition compared to their normally hearing peers, and that among listeners with normal hearing, age-related changes in hearing do not predict this age-related deficit. The present results also add to the literature by showing that hearing impairment contributes additionally to deficits in vocal emotion recognition, separate from deficits related to age. These effects of age and hearing loss appear to be quite robust, being evident in reduced accuracy scores and d’ measures, as well as in reaction time measures.